Minat Belajar Sejarah dan Implikasinya Terhadap Kesadaran Budaya di Madrasah Aliyah Negeri 2 Model - Putri, Fira Dwi; Rizki, Ainur (Medan Resource Center, 2024)
This study aims to analyze the interest in learning history among students of Madrasah Aliyah Negeri (MAN) 2 Model and its implications for their cultural awareness. Interest in learning history is considered a crucial factor in shaping students' understanding of cultural values and national identity. The study employs a descriptive quantitative approach using survey methods to measure students' interest in history lessons and the relationship between this interest and their cultural awareness. The results show that students with a high interest in learning history have a deeper understanding of traditional values, local wisdom, and Nusantara culture. Conversely, low interest in history learning tends to result in a lack of appreciation for the nation's cultural richness. These findings highlight the importance of innovation in history teaching methods, such as narrative-based approaches, interactive multimedia, and integrating local cultural values into the curriculum. Thus, increasing interest in history learning can significantly contribute to strengthening cultural awareness among students at Madrasah Aliyah Negeri 2 Model.